2022
DOI: 10.1103/physrevapplied.18.014067
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Points and Skin Modes in Non-Hermitian Metabeams

Abstract: We present a non-Hermitian metabeam exhibiting an exceptional point (EP) induced by enforcing parity-time (PT) symmetry through applied external forces. The EP is formed by the hybridization of two flexural wave modes and its output displacement is enhanced by attaching two pillars on top of the beam. The introduction of a tiny mass perturbation that breaks the PT symmetry leads to a splitting of the eigenfrequencies at the EP with a square-root dependence on the perturbation mass. This effect manifests itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…In general, a PT -symmetric 1D system features an asymmetric response from opposite sides, and such asymmetric behavior reaches an extreme at the EP, where unidirectional transparency or unidirectional reflectionlessness can be observed [104,108,150]. Beyond EPs, in the PT -broken phase, all bulk modes can be localized at a given boundary, which is known as the non-Hermitian skin effects (NHSEs) derived from the unconventional bulk-boundary correspondence in non-Hermitian systems [114,118,[151][152][153][154][155]. As will be discussed in section 4.6, NHSE is another important feature of the non-Hermitian system.…”
Section: Non-hermitian Acoustics In Waveguides (1d)mentioning
confidence: 99%
See 2 more Smart Citations
“…In general, a PT -symmetric 1D system features an asymmetric response from opposite sides, and such asymmetric behavior reaches an extreme at the EP, where unidirectional transparency or unidirectional reflectionlessness can be observed [104,108,150]. Beyond EPs, in the PT -broken phase, all bulk modes can be localized at a given boundary, which is known as the non-Hermitian skin effects (NHSEs) derived from the unconventional bulk-boundary correspondence in non-Hermitian systems [114,118,[151][152][153][154][155]. As will be discussed in section 4.6, NHSE is another important feature of the non-Hermitian system.…”
Section: Non-hermitian Acoustics In Waveguides (1d)mentioning
confidence: 99%
“…On the other hand, the ultra-high sensitivity of a system at EP essentially amplifies any small parametric variations, a useful property for sensor applications [167]. It has been shown that a non-Hermitian system operating in close vicinity of an EP, with the eigenfrequencies of the relevant non-Hermitian modes being highly sensitive to perturbations to the system [117,118,126,168], has potential applications in ultrasonic inspection, noise detection, and vibration accelerometer. Moreover, unidirectional transparency stemming from non-Hermitian acoustic systems can also be utilized to realize an acoustic directional cloak [104,110].…”
Section: Non-hermitian Acoustics In Waveguides (1d)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although all topological aspects of the NHSE -in contrast with Hermitian topological modes -can be studied in simpler single-band periodic systems with one degree of freedom per unit cell, distributed-parameter models with an infinite number of bands in the reciprocal space are more realistic in representing practical applications. This work makes contributions in this direction, using acoustic one-dimensional waveguides with periodically applied electroacoustic feedback, following a design strategy that emulates both nearest-neighborhood and long-range non-reciprocal coupling by applying local and non-local feedback interactions, respectively [24,25,30,20].…”
Section: Introductionmentioning
confidence: 99%
“…These systems may find a myriad of applications in engineering, wherever mechanical waves need to be localized and filtered. For instance, investigations suggest that they can be used as design strategies to control filaments and membranes in biological systems [20] and may also be highly effective for broad-band energy harvesting, when compared to traditional approaches [30].…”
Section: Introductionmentioning
confidence: 99%